1998
DOI: 10.1016/s0006-3495(98)77668-4
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Cell Wall Expansion Based on Thermodynamics of Polymer Networks

Abstract: A theory of cell wall extension is proposed. It is shown that macroscopic properties of cell walls can be explained through the microscopic properties of interpenetrating networks of cellulose and hemicellulose. The qualitative conclusions of the theory agree with the existing experimental data. The dependence of the cell wall yield threshold on the secretion of the wall components is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(57 citation statements)
references
References 33 publications
1
53
0
3
Order By: Relevance
“…Because many studies have shown that XyG forms strong noncovalent interactions with cellulose (for reviews, see Fry [1989], Hayashi [1989], Carpita and Gibeaut [1993], and Obel et al [2007]), XyG is featured prominently in many models of the primary cell wall. Most models predict that XyG functions as a tether by cross-linking adjacent cellulose microfibrils, thereby forming a cellulose-XyG network that functions as the primary load-bearing structure of the primary cell wall during cell expansion (Fry and Miller, 1989;Hayashi, 1989;McCann and Roberts, 1991;Passioura and Fry, 1992;Carpita and Gibeaut, 1993;Veytsman and Cosgrove, 1998;Somerville et al, 2004). Other models predict that XyG acts either as a spacer to prevent the cellulose microfibrils from aggregating (Thompson, 2005) or as an adapter that enables cellulose to interface with other cell wall matrix components (Keegstra et al, 1973;Talbott and Ray, 1992;Ha et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Because many studies have shown that XyG forms strong noncovalent interactions with cellulose (for reviews, see Fry [1989], Hayashi [1989], Carpita and Gibeaut [1993], and Obel et al [2007]), XyG is featured prominently in many models of the primary cell wall. Most models predict that XyG functions as a tether by cross-linking adjacent cellulose microfibrils, thereby forming a cellulose-XyG network that functions as the primary load-bearing structure of the primary cell wall during cell expansion (Fry and Miller, 1989;Hayashi, 1989;McCann and Roberts, 1991;Passioura and Fry, 1992;Carpita and Gibeaut, 1993;Veytsman and Cosgrove, 1998;Somerville et al, 2004). Other models predict that XyG acts either as a spacer to prevent the cellulose microfibrils from aggregating (Thompson, 2005) or as an adapter that enables cellulose to interface with other cell wall matrix components (Keegstra et al, 1973;Talbott and Ray, 1992;Ha et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The plant cell wall consists of a network of cellulose microfibrils 30 glued together by a polysaccharide matrix (ibid.). The primary wall is se-31 creted by the growing cell and is maintained in an extensible, plastic state 32 during the period of cell growth, before the cell matures and the wall loses 33 its ability to expand (Veytsman and Cosgrove, 1998). This process, from 34 the physical point of view, can be described by a dynamic extensibility co-35 efficient.…”
mentioning
confidence: 99%
“…The reduction in turgor pressure results in a cellular water uptake, which finally causes the expansion of the cell. Lockhart (1965) was one of the first to describe this interrelation of wall expansion and water uptake in a biophysical model, which was the basis for further approaches to take cell wall properties and the influence of water flow into account (Sellen 1983;Cosgrove 1993;Veytsman & Cosgrove 1998;Proseus et al 1999Proseus et al , 2000.…”
Section: (A ) Cell Growthmentioning
confidence: 99%